Revisión sistemática del concepto de polivictimización desde una perspectiva metodológica - Ortega Vidal, Beatriz (Revista Española de Investigación Criminológica, 2020)
The concept of polyvictimization, understood as the experimentation of multiple types of victimization during childhood and adolescence, is widely recognized. The development of the Juvenile Victimization Questionnaire has allowed a comprehensive study of this phenomenon. However, there is no agreement on the methodological definition, with multiple elements affecting the detection of polyvictims. The aim is to carry out a review of the concept of polyvictimization from a methodological perspective. It includes 30 articles describing the method of analysis, the timeframe analyzed, the type of sample and the version of the instrument applied. It discusses how this variability of methodological critea build a different methodological definition of polyvictimization in each reasearch, affecting the cut-off points and the detection of polyvictims groups. This work offers guidance to understand the prevalence of polyvictimization and can serve as a guide for new researchers in this field of study.